Maternal contact and positive human interactions during lactation impacts piglet performance and behaviour during lactation - Tomas, Katelyn; Savaglia, Jemma; Plush, Kate J.; D’Souza, Darryl N.; Butler, Kym L.; Hemsworth, Paul H.; Tilbrook, Alan J. (Frontiers in Animal Science, 2024)
Early life interactions with the sow or humans can have lifelong consequences on welfare and performance in pigs. It was hypothesised that piglets that received increased maternal contact and positive human contact would display improved responses to stressful events and improved performance. Ninety-eight litters were allocated to a 2 x 2 factorial design for maternal contact (MC+) / restricted maternal contact (MC-); and positive human contact (HC+) / no additional human contact (HC-). Modified farrowing crates were used to restrict maternal contact (MC-) and litters in the HC+ treatment received five minutes of daily positive human interaction (stroking). Behavioural and physiological responses were assessed during processing at three days of age and during a behaviour test in which piglets were introduced to an empty arena, novel object, human hand and human standing in the arena at 18 days of age. Observations of behaviour in the home pen and growth and survival of piglets to weaning were also assessed. At processing, MC- piglets had more squeals (P = 0.015), tended to have more grunts (P = 0.063) and struggle attempts (P = 0.079), and had increased plasma cortisol concentrations (P = 0.009) after processing than MC+ piglets. During the behaviour test, HC+ piglets were more active (P = 0.014) and had more vocalisations (P < 0.05) in the empty arena than HC- piglets. Furthermore, HC+ piglets were more likely to approach a human standing in the arena (P = 0.006) than HC- piglets. MC- piglets were less active (P = 0.008) and were less likely to approach the novel object (P = 0.049) than MC+ piglets. MC+ piglets tended to have higher weaning weights (P = 0.055) and more MC+ piglets were successfully weaned (P = 0.022) than MC- piglets. There was no significant effect of HC on piglet performance. While positive handling did not affect behavioural and physiological stress response to processing, HC+ reduced fear of novelty and humans. These findings highlight the importance of early life experiences has on stress resilience early in life.